Study of thermal aggregation and gelation of oat globulin by Raman spectroscopy. Issue 2 (2003) - Ma Ma, C. Y. C. Y.; Rout Rout, M. K. M. K.; Phillips Phillips, D. L. D. L.
Abstract : Thermal aggregation and gelation of oat globulin were studied by FT‒NIR Raman spectroscopy. The buffer‒soluble aggregates exhibited a Raman spectrum similar to that of the unheated control, whereas the insoluble aggregates showed intensity increases in the tryptophan, C–H bending and C–H stretching bands, and a decrease in the tyrosine doublet ( I 850 / I 830 ), suggesting protein denaturation. However, analysis of the amide I region using Raman Spectral Analysis Package (RASP) program revealed marked decreases in α ‒helical and increases in β ‒sheet structure in both soluble and insoluble aggregates. Similar conformational changes were also observed in the heat‒induced oat globulin gels, and may be attributed to realignment of molecular segments and formation of intermolecular β ‒sheet structures. Thermal gelation under the influence of different chaotropic salts showed some shifts in band positions and changes in band intensity, following the lyotropic series of anions. Several protein structure perturbants, including sodium dodecyl sulfate, dithiothreitol, urea and sodium laurate, were found to affect the Raman spectral characteristics of oat globulin gels. The data suggest that changes in gelling properties of oat globulin by these chemicals may be related to conformational changes of the protein during gelation.